Implementing Project-Based Learning to Improve Students' Engagement and Learning Outcomes in Basic Map-Making Skills: A Classroom Action Research Study at SMAN 4 Kupang - Regina Sarah Asamoi; Mikael Samin; Arfita Rahmawati (Tinta Emas Publisher, 2026)
Basic map-making is a foundational geography competency because it requires students to read spatial information, represent relief forms, and translate abstract geographic concepts into meaningful visual products. However, preliminary classroom conditions in Grade X-L at SMAN 4 Kupang indicated that geography learning was still perceived as memorization-oriented and teacher-centered, resulting in limited participation and low achievement. This classroom action research examined the implementation of Project-Based Learning (PjBL) through a waste-paper-based relief map project and evaluated its contribution to students' engagement, creativity, and learning outcomes. The research involved 36 students and was conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected using student and teacher observation sheets, project creativity assessment, and 15-item cognitive tests. The success criterion was set at a minimum mastery score of 75, with at least 75% of students achieving mastery. The findings showed consistent cross-cycle improvement. Student activity increased from a mean score of 2.91 in Cycle I to 3.67 in Cycle II, while project creativity increased from 50% to 78%. Cognitive achievement improved from an average score of 53.73 in Cycle I to 78.52 in Cycle II, and mastery rose from 50.00% to 80.56%. The normalized gain was 0.54, indicating a moderate improvement. These results suggest that PjBL supported more active, collaborative, and product-oriented geography learning, particularly when basic map-making was connected with spatial representation and environmental reuse.